Body composition and nutritional profile of male adolescent tennis players - Juzwiak, C. R.; Amancio, O. M. S.; Vitalle, M. S. S.; Pinheiro, M. M.; Szejnfeld, V. L. (Journal of Sports Sciences, 2008)
In this cross-sectional study, we evaluated the body composition and dietary intake of 44 adolescent tennis players. After being divided into two groups (age 10-13 years and age 14-18), the players had their weight, height, and sexual maturation assessed. Dual-energy X-ray absorptiometry was used to assess body composition. Food intake was obtained from a non-consecutive 4-day food record. The data were analysed using the Virtual Nutri v.1.0 software and compared with the present recommendations for adolescent athletes or dietary reference intakes. Body mass index and body fat for tennis practice were adequate for 89% and 71% of the tennis players respectively, regardless of age group. A calorie deficit greater than 10% of energy expenditure was observed in 32% of the sample. Fifty percent of the athletes consumed carbohydrates in accordance with recommended values. Protein and lipid intakes were above recommended values, while fibre, calcium, potassium, magnesium, and folic acid intakes were below recommendation for 98%, 80%, 100%, 100%, and 98% of the tennis players respectively. The observed nutritional deficiencies represent an additional barrier for adolescents engaged in competitive sports to achieve an optimum nutrition to maintain growth, health, and performance.